African language use in the digital public sphere: functionality of the localised Google webpage in Zimbabwe - Mpofu, Phillip; Salawu, Abiodun (Routledge, 2022)
The widely used web search engine in Zimbabwe, Google, offers a localised webpage with an option to change the language from English to African languages for users to find information using their favoured languages. This article interrogates the practicality of the localised Google webpage which is also available in ChiShona, IsiNdebele, Chichewa and Setswana, over and above English, the main language. The enquiry employs the qualitative research approach, specifically the survey method. Empirical data were collected from conveniently and purposively selected African language academics and students using unstructured questionnaires, personal and group interviews. Elements of linguistic imperialism and electronic colonisation concepts are deployed to explain African language use on the Internet, in the context of English language dominance in Zimbabwe and the global digital divide. While localisation of the Google webpage to some extent demonstrates global multilingual inclusivity, the article shows its redundancy in the context of present language policy and practices that promote English. We maintain that while the discourse of linguistic inclusivity is important and applauded, presently the localised Google webpage is ineffectual due to the entrenched English language hegemony nationally, and on the Internet. This study is a significant addition to the burgeoning body of scholarship on African language use in the digital public sphere.